The antidepressant drug sertraline is a novel inhibitor of yeast Pah1 and human lipin 1 phosphatidic acid phosphatases - Geordan J. Stukey; Matthew R. Breuer; Natalie Burchat; Ruta Jog; Kollin Schultz; Gil-Soo Han; Matthew S. Sachs; Harini Sampath; Ronen Marmorstein; George M. Carman (Journal of Lipid Research)
Phosphatidic acid phosphatase (PAP) is an evolutionarily conserved eukaryotic enzyme that catalyzes the Mg2+-dependent dephosphorylation of phosphatidic acid to produce diacylglycerol. The product and substrate of PAP are key intermediates in the synthesis of triacylglycerol and membrane phospholipids. PAP activity is associated with lipid-based cellular defects indicating the enzyme is an important target for regulation. We identified that the antidepressant sertraline is a novel inhibitor of PAP. Using Saccharomyces cerevisiae Pah1 as a model PAP, sertraline inhibited the activity by a noncompetitive mechanism. Sertraline also inhibited the PAP activity of human lipin 1 (α, β, and γ), an orthologue of Pah1. The inhibitor constants of sertraline for the S. cerevisiae and human PAP enzymes were 7-fold and ∼2-fold, respectively, lower than those of propranolol, a commonly used PAP inhibitor. Consistent with the inhibitory mechanism of sertraline and propranolol, molecular docking of the inhibitors predicts that they interact with non-catalytic residues in the haloacid dehalogenase-like catalytic domain of Pah1. The Pah1-CC (catalytic core) variant, which lacks regulatory sequences, was inhibited by both drugs in accordance with molecular docking data. That Pah1 is a physiological target of sertraline in S. cerevisiae is supported by the observations that the overexpression of PAH1 rescued the sertraline-mediated inhibition of pah1Δ mutant cell growth, the lethal effect of overexpressing Pah1-CC was rescued by sertraline supplementation, and that a sublethal dose of the drug resulted in a 2-fold decrease in TAG content.